Exploring The Plot Analysis 'Kami (bukan) Sarjana Kertas Novel': Seeking for Charactersâ€™ Problems - Saltri Yudar, Ratih; Sari Gowasa, Nofita; Sari Nursafira, Mutia (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
This research purposes to analyze the plot of novel written by Indonesian writer named J.S Khairen entitled â€œKami (Bukan) Sarjana Kertasâ€. Chooses this novel because the idea or main story of this novel related to how young people these days recognizing their own passions, how they struggling from many problems that come on their journey to reach their dreams. This analysis using qualitative research as its methodology to identify the plot of this novel. Novel as a part of prose in literature has two elements, such as intrinsic and extrinsic elements. However this study only focuses its analysis on the intrinsic elements. This study revealed the plot as a structure of events, which is as shown in the arrangement and presentation of the events to accomplish a certain artistic value. The plot is manifested through acts, manner, and attitude of story main characters based on Teori Pengkajian Fiksi proposed by Nurgiyanto (2012).